2018
DOI: 10.1002/jcc.25613
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and rate constants of the CH2 + CH2CO reactions in triplet and singlet states: A theoretical study

Abstract: Ab initio and density functional CCSD(T)-F12/cc-pVQZ-f12// B2PLYPD3/6-311G** calculations have been performed to unravel the reaction mechanism of triplet and singlet methylene CH 2 with ketene CH 2 CO. The computed potential energy diagrams and molecular properties have been then utilized in Rice-Ramsperger-Kassel-Marcus-Master Equation (RRKM-ME) calculations of the reaction rate constants and product branching ratios combined with the use of nonadiabatic transition state theory for spin-forbidden triplet-sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Konnov and co-workers , showed the importance of CH 2 CO chemistry during the modeling of diacetyl and acetic acid flames. In the light of their findings, we updated the CH 2 CO submechanism based on the results of recent theoretical works. Again, we note that the available kinetic models in the literature could not accurately predict the laminar flame speed of CH 3 CHO–air mixtures. With the current updates, our model showed a significantly improved performance while predicting the available experimental literature data over a wide range of conditions.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…Konnov and co-workers , showed the importance of CH 2 CO chemistry during the modeling of diacetyl and acetic acid flames. In the light of their findings, we updated the CH 2 CO submechanism based on the results of recent theoretical works. Again, we note that the available kinetic models in the literature could not accurately predict the laminar flame speed of CH 3 CHO–air mixtures. With the current updates, our model showed a significantly improved performance while predicting the available experimental literature data over a wide range of conditions.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…The 4PN molecule is a prototypical cyclic enone and serves as a model for investigating the π* ← n chromophore in α,β-unsaturated carbonyls. Triplet excited states of unsaturated molecules can play key roles in photochemistry, 1 combustion, 2 and energy storage. 3 Triplet excited states are generally long-lived, enhancing their abiliity to participate in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Ketene (CH 2 CO) is a key intermediate in the combustion of hydrocarbons and oxygenated fuels. Its formation and consumption pathways are an essential part of the C 0 –C 4 combustion core mechanisms. One of the latest ketene mechanisms was developed by Konnov et al However, subsequent theoretical studies suggested that rate parameters of several important reactions in the mechanism need modifications. Pyrolysis of ketene was investigated directly in early shock tube studies, ,, but due to its high reactivity, the preparation of a pure ketene sample is challenging. Therefore, indirect experiments in which ketene is produced as an intermediate were preferred in recent fundamental combustion experiments. ,,, Diacetyl ((CH 3 CO) 2 ) is one of the optional fuels that can be used as a precursor of ketene, and the reaction processes from diacetyl to ketene and corresponding mechanisms attracted interest. ,, …”
Section: Introductionmentioning
confidence: 99%